2017
DOI: 10.3389/fpsyt.2017.00178
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Accessibility of a Tailored Intervention for Informal Caregivers of People with Severe Psychiatric Disorders: a Pilot Study

Abstract: ObjectivesThis study aimed to assess the acceptability and feasibility of a new tailored intervention for informal caregivers: the Ensemble (Together) program.MethodsAn open pre–post within-subject comparison pilot study was conducted. Twenty-one informal caregivers completed the five-session Ensemble program. Two measurement tools were used: The Brief Symptom Inventory (BSI) and the Life Orientation Scale (LOT-R).ResultsThe results showed that informal caregivers were in need of individual support and were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 57 publications
(60 reference statements)
1
18
0
Order By: Relevance
“…A 2008 French-language version of LOT-R was validated using 208 Francophone university students. This demonstrated that the French-language version possessed satisfactory psychometric properties comparable with those of the English-language version (Cronbach's alpha, 0.76; test-retest reliability, 0.74) (39,43).…”
Section: The Life Orientation Test-revisedmentioning
confidence: 88%
See 2 more Smart Citations
“…A 2008 French-language version of LOT-R was validated using 208 Francophone university students. This demonstrated that the French-language version possessed satisfactory psychometric properties comparable with those of the English-language version (Cronbach's alpha, 0.76; test-retest reliability, 0.74) (39,43).…”
Section: The Life Orientation Test-revisedmentioning
confidence: 88%
“…According to Priestley & McPherson, even if caregivers can adapt to depression, they look to the future with hope but also apprehension due to the unpredictability of depression (19). To better support informal caregivers in their process of psychological recovery, individualized brief programs are recommended (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, caregivers who belong to underserved communities are most likely to experience worse levels of caregiver burden. This worrying nding underscores the urgent need for timely and effective interventions that could alleviate these underserved populations' caregiver burden, such as intervention programs that are tailored to these caregivers' unique unmet needs [50][51][52]. As these disadvantaged caregivers are often di cult to reach via traditional intervention measures [53,54], researchers may consider using more agile and exible programs, such as local reach programs [55][56][57][58][59] or technology-based solutions [60,61], to deliver relevant and effective health solutions to these caregivers in a convenient and cost-effective fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Also, co-operation and support from psychiatric services is regarded as crucial to the success of municipality programs. In the last years there has been a development of peer-to-peer family programs run by municipalities (Lucksted et al 2013 ; Rexhaj et al 2017 ). These programs have shown improved satisfaction for relatives of consumers with SMI in their daily lives, independent of professional support (Lucksted et al 2013 ; Pickett-Schenk et al 2008 ; Rexhaj et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%